2012
DOI: 10.1108/10662241211199942
|View full text |Cite
|
Sign up to set email alerts
|

How social identification and trust influence organizational online knowledge sharing

Abstract: Purpose -The purpose of this study is to propose a conceptual structural equation model to, first, investigate the relationships among knowledge management (KM) system quality, employees' self-perceived social identification, trust at workplace as well as online knowledge sharing behaviors, and, second, demonstrate the direct and indirect effect of social identification and trust at workplace on online knowledge sharing from the perspective of KM system quality. Design/methodology/approach -A questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 87 publications
11
70
0
2
Order By: Relevance
“…Therefore, IT is considered as an indispensable tool that supports discovery of useful knowledge (Ho et al, 2012). Collaborative tools such as intranet based systems allow people to work together and collaborate interactively.…”
Section: Technology Infrastructurementioning
confidence: 99%
“…Therefore, IT is considered as an indispensable tool that supports discovery of useful knowledge (Ho et al, 2012). Collaborative tools such as intranet based systems allow people to work together and collaborate interactively.…”
Section: Technology Infrastructurementioning
confidence: 99%
“…Hence, organisations use technological infrastructure to create and disseminate knowledge within organisations (Ryan et al 2010). The effective use of ICT guarantees well-timed access and sharing of knowledge for decision-making processes (Ho, Kuo & Lin 2012). This study found that inadequate and underdeveloped ICT is a major barrier to knowledge sharing in Limpopo municipalities.…”
Section: Discussion Of the Findingsmentioning
confidence: 83%
“…Finally, Section 5 concludes this paper. Thompson (2008) To make use of Facebook for highly sophisticated privacy control Ethics (privacy) Light and McGrath (2010) This study attempts to integrate social networks with sports lottery communities to enhance trust Ethics (trust) Protection configurations Acquisti and Gross (2006), Light and McGrath (2010), Karyda et al (2009) Schoen et al (2013) To support users with a communication platform to post and share information with each other Self-service Lin and Huang (2013), Ho et al (2012) To allow users to decide the prediction rate of betting games through multiple mechanisms, including votes, odds, and future events, not only single mechanism Prediction method Future events Decision support Taylor et al (2004) The related messages are aggregated into a game blog, which is a type of community blog Data integration Lin and Huang (2013) To provide users with statistical reports to enable them to verify their voting and betting decisions Prediction Ciou (2010) The prediction price can be used as a reference to predict whether an event occurs Prediction Future events The interactive strategies, such as interacting with Facebook in real time, posting and agentbased gift delivering functions, were designed to facilitate interaction among users Interactive Moreira et al (2013) Although several web analytics products and services are available, such as Google Analytics, for testing and evaluating a website, but such types of tools are not suitable for use Web development method Nakatani and Chuang (2011) A prototyping website development methodology Prototyping development method Che and Hou (2008) To identify the main stages and tasks involved in website development Prototyping development method Questionnaire Schefels and Zicari (2012) …”
Section: Intr 263mentioning
confidence: 99%